2019
DOI: 10.6000/1929-5995.2019.08.01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Foaming Agent in Enhancing Dispersion of Montmorillonite in Polypropylene Nanocomposite

Abstract: Homogenous dispersion of the nano particles in the polymer matrix is a key factor in order to achieve enhanced properties of the polymer nanocomposites. Dispersion or exfoliation of nano clay is difficult in the matrix during melt mixing. In this study, dispersion of nano montmorillonite (MMT) in polypropylene (PP) was done by using chemical foaming agent during melt mixing process. Chemical foaming agent (CFA) added (1 %wt.) PP/MMT nanocomposites were prepared on twin screw extruder. Then, injection molding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, there are several studies in the literature that examine the effect of foaming agent ratio on the properties of polypropylene and polypropylene-based composites. 8,11,[28][29][30][31][32] Guo et al 11 studied polypropylene with branched and plain chain structure and concluded that the cell diameter decreased while cell density increased with the increase in azo-di-carbon-amide type foaming agent from 1 wt.% to 2 wt.% Cakir et al 28 investigated the effect of chemical foaming agent on mechanical properties of PP based foam materials. Chemical foaming agent was used in different proportions (1, 1.5, 2, 2.5, 3 wt.%).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are several studies in the literature that examine the effect of foaming agent ratio on the properties of polypropylene and polypropylene-based composites. 8,11,[28][29][30][31][32] Guo et al 11 studied polypropylene with branched and plain chain structure and concluded that the cell diameter decreased while cell density increased with the increase in azo-di-carbon-amide type foaming agent from 1 wt.% to 2 wt.% Cakir et al 28 investigated the effect of chemical foaming agent on mechanical properties of PP based foam materials. Chemical foaming agent was used in different proportions (1, 1.5, 2, 2.5, 3 wt.%).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies in the literature involved the foaming of the polyamide, polystyrene, polylactic aside (PLA), low density polyethylene (LDPE), high density polyethylene (HDPE), polyvinyl chloride (PVC), polyoxymethylene (POM), polypropylene (PP), epoxy polymers and ethylene-propylene-dien rubber (EPDM), epoxy and some rubber materials. 11-32 Hussein et al 16 studied the effect of the amount of endothermic sodium bicarbonate foaming agent on the mechanical and physical properties of epoxy foams. They stated that, viscosity increased, density, bending strength and flexural modulus values decreased with increasing the sodium bicarbonate amount.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation